KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH - Gusnaini Gusnaini; Darmawan Darmawan; Besse Herlina; Jusma Jusma; Sri Rahayu; Masriadi Masriadi; Indo Wellang (Jurnal Manajemen Pendidikan, 2026)
School leadership is a key determinant of education quality, requiring principals who can inspire, motivate, and foster teacher commitment to create a positive work culture and effective learning. This study aims to explain the concept of transformational leadership, describe its implementation by school principals, and examine its impact on improving teacher performance. The research employed a descriptive qualitative approach using observation, documentation, and literature review of relevant studies, with principals and teachers as the main subjects.The findings reveal that principals apply transformational leadership through role modeling, providing motivation and recognition, involving teachers in decision-making, and encouraging innovation in teaching. These practices lead to increased discipline, creativity, and teacher self-confidence, while fostering a harmonious work environment. The novelty of this study lies in highlighting the contextual application of transformational leadership in Indonesian schools, emphasizing the integration of local cultural values with leadership practices. The study concludes that transformational leadership is effective in enhancing teacher motivation and performance while strengthening positive school culture. Practical implications suggest the need for leadership training, managerial competence development, and collective reflection among educators.